PHOTO DYNAMIC THERAPY (PDT) WITH BIOLOGICAL TISSUES USING ND:GLASS LASER (Journal of Engineering, 2011)
A Photo Dynamic Therapy (PDT) is a technique which is used with Laser to treat many of cancertissues. This paper deals with the relatively new therapeutic technique (PDT) with pulsed Nd:glass Laserwhich was applied to human soft tissues (Ovary and Kidney tissues), and to the hard tissues (freshlyextracted human teeth), with power density of 280 watt/mm2 and exposure time 330 usec. Differentdyes (Blue, methylene, eosin, and orange) were applied to the area before irradiation to study the effectof the pigments on the laser interaction with biological tissues. The zone of treatment (Z-necrosis) withaid of MATLAB was determined. The relationship of zone of treatment with exposure time,accumulated damage and fraction of oxidative radicals was obtained.